2018
DOI: 10.1103/physrevd.97.095010
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap of left-right models based on GUTs

Abstract: We perform a detailed study of the grand unified theories SO (10) and E(6) with left-right intermediate gauge symmetries of the form SU (N ) L ⊗ SU (N ) R ⊗ G. Proton decay lifetime constrains the unification scale to be 10 16 GeV and, as discussed in this paper, unwanted cosmological relics can be evaded if the intermediate symmetry scale is 10 12 GeV. With these conditions, we study the renormalisation group evolution of the gauge couplings and do a comparative analysis of all possible left-right models wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 142 publications
(222 reference statements)
0
37
0
Order By: Relevance
“…So their presence may affect the matching conditions as well in the form of threshold corrections. In the absence of these threshold corrections, the detailed matching conditions for different scenarios are discussed in [7]. These conditions get modified in the presence of threshold corrections [62,[89][90][91][92][93][94][95][96][97].…”
Section: Matching Conditions and Threshold Correctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…So their presence may affect the matching conditions as well in the form of threshold corrections. In the absence of these threshold corrections, the detailed matching conditions for different scenarios are discussed in [7]. These conditions get modified in the presence of threshold corrections [62,[89][90][91][92][93][94][95][96][97].…”
Section: Matching Conditions and Threshold Correctionsmentioning
confidence: 99%
“…In this paper, we estimate the proton lifetime in a wide class of non-supersymmetric GUTs, broken via left-right subgroups with one or two intermediate scales For the one intermediate scale breaking, we suppose that the GUT groups break into their maximal subgroups of the form SU (N ) L ⊗ SU (N ) R ⊗ G, see [7]. This restricts our choice of GUT groups to be SO(10), E (6), with certain breaking patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to allow gauge coupling unification, we need SUSY, but we shall assume it is broken above the Z 0 BLR mass scale so that SUSY particles are not present in the decays of the Z 0 BLR . Note that such SUSY decays have been considered extensively in [12][13][14][15][16][17][18].…”
Section: Modelmentioning
confidence: 99%
“…It was recently realized that SUSY SOð10Þ models which break down to this gauge group may allow for a new type of seesaw model, namely the linear seesaw model [10,11]. Subsequently, the phenomenology of the SUSY Uð1Þ R × Uð1Þ B−L model has been studied in a number of works [12][13][14][15][16][17][18]. Indeed, it has been demonstrated that the Abelian BLR gauge group Uð1Þ R × Uð1Þ B−L is equivalent to Uð1Þ Y × Uð1Þ χ [arising from the breaking chain in Eq.…”
Section: Introductionmentioning
confidence: 99%